2007
DOI: 10.1161/01.res.0000260804.77807.cf
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Splicing of Ryanodine Receptors Modulates Cardiomyocyte Ca 2+ Signaling and Susceptibility to Apoptosis

Abstract: Abstract-Ca2ϩ release via type 2 ryanodine receptors (RyR2) regulates cardiac function. Molecular cloning of human RyR2 identified 2 alternatively spliced variants, comprising 30-and 24-bp sequence insertions; yet their role in shaping cardiomyocyte Ca 2ϩ signaling and cell phenotype is unknown. We profiled the developmental regulation and the tissue and species specificity of these variants and showed that their recombinant expression in HL-1 cardiomyocytes profoundly modulated nuclear and cytoplasmic Ca 2ϩ r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
50
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 28 publications
4
50
0
Order By: Relevance
“…A 24-bp exon in RYR2 is upregulated in Rbm20-deficient rats and human cardiomyopathy patients ( Figure 6A). This exon is usually present at low levels in hearts and shifts RYR2 from the ER to the intranuclear Golgi apparatus, with profound effects on intracellular Ca 2+ signaling (27). Mutations in N-terminal domains of RYR2 have been associated with arrhythmogenic right ventricular tachycardia and sudden death (28).…”
Section: Regulatory Impact Of Rbm20 On Cardiomyopathy-associated and mentioning
confidence: 99%
“…A 24-bp exon in RYR2 is upregulated in Rbm20-deficient rats and human cardiomyopathy patients ( Figure 6A). This exon is usually present at low levels in hearts and shifts RYR2 from the ER to the intranuclear Golgi apparatus, with profound effects on intracellular Ca 2+ signaling (27). Mutations in N-terminal domains of RYR2 have been associated with arrhythmogenic right ventricular tachycardia and sudden death (28).…”
Section: Regulatory Impact Of Rbm20 On Cardiomyopathy-associated and mentioning
confidence: 99%
“…Alternative splicing may affect the protein sequence in two ways: (i) by deleting or inserting a sequence and creating long and short isoforms, or (ii) by substituting one segment of the amino acid sequence for another [54]. It was reported that 12 distinct splice variants had been identified in RyR isoforms cloned from mammals [55]. The expressions of RyR splice variants in mammals are regulated both developmentally and in a tissuespecific manner among RyR isoforms [55][56][57][58], and some splice variants can suppress intracellular Ca 2+ fluxes or exhibit distinct Ca 2+ -releasing profiles [10,59,60].…”
mentioning
confidence: 99%
“…It was reported that 12 distinct splice variants had been identified in RyR isoforms cloned from mammals [55]. The expressions of RyR splice variants in mammals are regulated both developmentally and in a tissuespecific manner among RyR isoforms [55][56][57][58], and some splice variants can suppress intracellular Ca 2+ fluxes or exhibit distinct Ca 2+ -releasing profiles [10,59,60]. In contrast to mammals, only one RyR gene was found in insects, which showed only a 44 to 46% amino acid identity with the three mammalian RyRs [20].…”
mentioning
confidence: 99%
“…Three major isoforms (RyR1, RyR2 and RyR3) and several spliced variants of RyR are present in mammalian cells (Takeshima et al, 1989;Otsu et al, 1990;Zorzato et al, 1990;Hakamata et al, 1992;Futatsugi et al, 1995;Giannini et al, 1995;Conti et al, 1996;Leeb and Brenig, 1998;Jiang et al, 2003;George et al, 2007). Some organs contain a predominance of one RyR isoform, for example skeletal muscles contain primarily RyR1 (Takeshima et al, 1989;Zorzato et al, 1990) and the heart contains mainly RyR2 (Otsu et al, 1990).…”
Section: A Transient Rise In Intracellular Camentioning
confidence: 99%